PENGARUH TANAMAN SELA TERHADAP PERTUMBUHAN TANAMAN KARET MUDA PADA SISTEM PENEBANGAN BERTAHAP - Yulius Ferry; Dibyo Pranowo; Rusli Rusli (Jurnal Tanaman Industri dan Penyegar, 2013)
The gradual rejuvenation in rubber plantation (Hevea brasiliensis) is one alternative of rejuvenation model that able to be carried out by farmers. Hypotetically, the difference in logging percentage can effect on the growth of young rubber plant and intercrops. The objectives of this research was to investigate the effect of intercrops (corn and peanuts) on the growth of young rubber plant in gradual logging system. The research has been carried out in smallholders rubber plantation in Way Kanan, North Lampung, from January to December 2012. The study was designed by split plot design with 3 replications. The main plot are the logging percentage, (P1) 30%, (P2) 50%, (P3) 70%, and (P4) 100%, and the subplot are the kind of intercrops: corn and peanuts. The results showed that corn as intercrop in logging percentage of 30%, 50%, and 70% did not effect on the stem diameter of young rubber, but if peanut as intercrops can inhibit the growth of stem diameter of young rubber. The logging percentage of 70% did not effect on the growth and yield of corn and peanut as intercrops.